Kondisi Desain Kemasan Produk Makanan Ringan Dan Minuman Instant Pada Industri Kecil Skala Rumah Tangga (Micro Industry) Di Kabupaten Kediri - Natadjaja, Listia; Cahyono, Yohanes Budi; Yuwono, Elisabeth Christine (Nirmana, 2009)
The research explores the packaging design general condition at Kabupaten Kediri. The purpose of this research is to get a clear description from many parts like: producer, seller and consumer about Kabupaten Kediri’s products and packaging design these days. The research used qualitative method through deep interview with key person, open questioner and supported by quantitative method based on questioner. Hopefully, this research data and fact’s could be useful for every part especially micro industry’s reference to develop their product quantity and their packaging design quality.